Decision Points in Academic Leadership Development as an Engaged Scholar: To Lead or Not to Lead - Nicole Thompson; Nancy Franz (The University of Alabama, 2022)
Academics have a variety of career paths available to them, yet it can be difficult to determine what career opportunities will lead to beneficial professional and personal outcomes. As engaged scholars, we seek academic leadership positions that allow us to make a difference in the world, either directly or indirectly, using our unique skills, experience, teaching, and research. To help engaged scholars determine if academic leadership opportunities are appropriate for their aspirations, this article provides career paths experienced by two engaged scholars, criteria they use to select or forgo leadership positions, and lessons they've learned as academic leaders who are also engaged scholars.